2020
DOI: 10.1242/dev.185975
|View full text |Cite
|
Sign up to set email alerts
|

SIX1 and SIX4 homeoproteins regulate PAX7+ progenitor cell properties during fetal epaxial myogenesis

Abstract: Pax7 expression marks stem cells in developing skeletal muscles and adult satellite cells during homeostasis and muscle regeneration. The genetic determinants that control the entrance into the myogenic program and the appearance of PAX7+ cells during embryogenesis are poorly understood. SIX homeoproteins are encoded by the sine oculis-related homeobox Six1-Six6 genes in vertebrates. Six1, Six2, Six4 and Six5 are expressed in the muscle lineage. Here, we tested the hypothesis that Six1 and Six4 could participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 109 publications
(149 reference statements)
0
8
0
Order By: Relevance
“…During fetal myogenesis, PAX7-positive progenitor cells progressively exit cell cycle and by E16.5 they progressively adopt a satellite cell position, under the basal lamina (Esteves de Lima et al, 2014;Gros et al, 2005;Kassar-Duchossoy, 2005;Ontell and Kozeka, 1984;Picard and Marcelle, 2013;Relaix et al, 2005). This specific positioning of the progenitor cells under the basal lamina is regulated by the SIX1 and SIX4 transcription factors: in the Six1;Six4-null embryos PAX7-positive cells are impaired and do not adopt a homing position in the trunk muscles (Wurmser et al, 2020). In addition, NOTCH activity in progenitor cells is required to stimulate the production of their own basal lamina environment and to adhere to the fibers (Baghdadi et al, 2018;Bröhl et al, 2012).…”
Section: Embryonic and Fetal Myogenesismentioning
confidence: 99%
“…During fetal myogenesis, PAX7-positive progenitor cells progressively exit cell cycle and by E16.5 they progressively adopt a satellite cell position, under the basal lamina (Esteves de Lima et al, 2014;Gros et al, 2005;Kassar-Duchossoy, 2005;Ontell and Kozeka, 1984;Picard and Marcelle, 2013;Relaix et al, 2005). This specific positioning of the progenitor cells under the basal lamina is regulated by the SIX1 and SIX4 transcription factors: in the Six1;Six4-null embryos PAX7-positive cells are impaired and do not adopt a homing position in the trunk muscles (Wurmser et al, 2020). In addition, NOTCH activity in progenitor cells is required to stimulate the production of their own basal lamina environment and to adhere to the fibers (Baghdadi et al, 2018;Bröhl et al, 2012).…”
Section: Embryonic and Fetal Myogenesismentioning
confidence: 99%
“…Both Six5 and Six4 were identified to function together during vertebrate body wall development where loss of both genes resulted in omphalocele ( Takahashi et al, 2018 ). Further mouse compound knock-out studies have uncovered Six4 functional cooperation with Six1 during myogenesis ( Grifone et al, 2005 ; Relaix et al, 2013 ; Wurmser et al, 2020 ), gonadogenesis ( Fujimoto et al, 2013 ); thymus development ( Zou et al, 2006 ), neurogenesis ( Konishi et al, 2006 ; Chen et al, 2009 ), and kidney development ( Kobayashi et al, 2007 ; Xu and Xu, 2015 ). Based upon these studies, it appears Six4 function is compensated by other family members but still plays an important supportive role during embryonic development.…”
Section: Congenital Disease and Associated Developmental Biologymentioning
confidence: 99%
“…To date, SIX/TGF-β networks have not been thoroughly studied during embryonic development. However, components of the TGF-β pathway were found to be downregulated in Six1 / Six4 double knockout mouse Pax7 + muscle precursor cells ( Wurmser et al, 2020 ) while Six2 expression in metanephric mesenchyme progenitor cells may be controlled by TBRII/Smad3 ( Mao et al, 2017 ).…”
Section: Common Themesmentioning
confidence: 99%
“…Zbtb20 was previously described by Alonso-Martin et al (2016) to be one of the key genes induced in muscle stem cells and involved in myogenic progression. The downregulation of Pax7 and Hmcn2, on the other hand, points at both the deranged myogenic capacity as well as the poor cross-interactions with other cells, as Hmcn2 is a key gene coding for ECM proteins which allows for efficient Pax7+ cell homing in skeletal muscle (Faralli et al, 2011;Wurmser et al, 2020). In the upregulated gene pool, Pgam1 promotes cancer cell migration (Zhang et al, 2017), while Ppia has been shown to be correlated with poor prognosis in patients with hepatocellular carcinoma (Wang and Yu, 2019).…”
Section: Rna-seq Of Murine Rms Model Unveils Key Signature Compared To Satellite Cellsmentioning
confidence: 99%